Endoscopic Appearance of the Gastroesophageal Valve and Competence of the Cardia. Issue 3 (1996) - Ismail, T.; Bancewicz, J.; Barlow, J.
Abstract : The endoscopic appearance of the gastroesophageal valve, viewed by the retroflexed gastroscope, has been studied in 51 patients with and without reflux esophagitis. Esophagitis was graded according to its severity, and the yield pressure (YP) was measured in all patients to assess the competence of the cardia. There was a close relationship between the YP and the grades of the gastroesophageal valve. YP was significantly lower in patients with endoscopic oesophagitis than in patients with no evidence of reflux esophagitis ( p <0.0001). An increased abnormality of the gastroesophageal valve was associated with all grades of esophagitis and with a low YP. The valve mechanism at the cardia has an important role in determining its competence. YP is possibly a measure of the flap valve component of the gastroesophageal junction.